Análise da relação entre estabilidade funcional e rigidez passiva de tornozelo avaliadas por meio de duas medidas clínicas - Marcela Tamiasso Vieira (2016)
Tissue or joint stiffness seems to contribute to joint stability in both static and dynamic activities. Clinical measurements for assessing both joint stiffness and stability have been used in research contexts and clinical practice. The aim of the present study was to evaluate whether the relationship between passive joint stiffness and joint stability can be revealed when these properties are evaluated through clinical tests. We also investigated whether the relationship between these variables is different between sedentary and physically active individuals. Data collection consisted of two clinical evaluation tests, one-leg support functional stability assessment, the Star Excursion Balance Test (Star Test), and a clinical measure of passive ankle dorsiflexion stiffnessassessment, the "first detectable resistance position". Ankle dorsiflexion range of motion with a weight-bearing test was also evaluated as a control variable. The Pearson correlation coefficient was used to verify the relationship between the evaluated variables. To be shown the association between stiffness and stability described in the literature (greater stiffness, greater stability), the correlation between the clinical measure of stiffness and the reach distances of the Star Test should benegative. Considering the total sample (n = 72), a moderate and positive association was observed between the values obtained in the clinical test of passive stiffness and the anterior reach distance of the Star Test (r = 0.55; p <0.0001) in both lower limbs. This association remained moderate in the group of active individuals (r = 0.57 and p <0.0001 for the dominant lower limb (LL); r = 0.62 and p <0.0001 for non-dominant LL)and was weak for the group of sedentary individuals (r = 0.45 and p = 0.006 for dominant LL, r = 0.34 and p = 0.04 for non-dominant LL). In addition, a weak and negative relationship was observed between the values of the stiffness test and the posteromedial reach distance only in the non-dominant LL and especially in the group of active individuals (r = -0.38; p = 0.02). A relationship was also observed between the amount of dorsiflexion movement available in the joint with distances from the StarTest and with passive stiffness. Thus, the relation between stiffness and stability properties, as described in the literature, was not revealed considering the anterior reach distance, with the exception of the posteromedial reach distance. However, the results do not invalidate the use of these clinical tests for the measurement of the clinical properties in question.